2016
DOI: 10.1002/hyp.11053
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of instantaneous peak flow from maximum mean daily flow by regionalization of catchment model parameters

Abstract: Regionalization methods have been effectively used in many hydrological studies, such as regional flood frequency analysis and low flows. However, there is no study to estimate the instantaneous peak flow (IPF) from maximum mean daily flow (MDF) using hydrological models with regionalized parameters. In this paper, the semidistributed conceptual hydrological model Hydrologiska Byråns Vattenbalansavdelning is operated on a daily time step for 18 catchments in the Aller‐Leine basin, Germany. The model is calibra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 37 publications
0
7
0
1
Order By: Relevance
“…(2017) e Ding et al (2016) também encontraram bons ajustes entre as frequências observadas e simuladas pela distribuição GEV, contudo ressalta-se que nesses estudos os parâmetros da função foram estimados pelo método de Momentos-L. Costa et al (2019). Os autores também estimaram as vazões máximas para diferentes tempos de retorno variando de 2 a 100 anos.…”
Section: Resultsunclassified
“…(2017) e Ding et al (2016) também encontraram bons ajustes entre as frequências observadas e simuladas pela distribuição GEV, contudo ressalta-se que nesses estudos os parâmetros da função foram estimados pelo método de Momentos-L. Costa et al (2019). Os autores também estimaram as vazões máximas para diferentes tempos de retorno variando de 2 a 100 anos.…”
Section: Resultsunclassified
“…In this study, the non‐linearity was found even in the case that runoff mechanisms were explained by the catchment water storage alone. Estimating IPFs from daily flows has been an open question for almost a century, and various methods are still being proposed (e.g., Dastorani, Koochi, Darani, Talebi, & Rahimian, ; Ding et al, ; Ding & Haberlandt, ; Taguas et al, ). Given the high sensitivity of rainfall–runoff modelling to coarsening temporal scales (Cristiano et al, ; Ochoa‐Rodriguez et al, ), it would be better to incorporate a tool that acceptably converts daily flows to IPFs in bottom‐up assessments rather than depending on daily runoff estimates.…”
Section: Discussionmentioning
confidence: 99%
“…We selected a HBV-like conceptual model because it has shown good results in i) many regionalisation studies (e.g., Parajka et al, 2005;Jin et al, 2009;Singh et al, 2012;Wallner et al, 2013;Zelelew and Alfredsen, 2014;Beck et al, 2016;Neri et al, 2020); and ii) catchments with diverse hydroclimatic and geomorphological characteristics (Merz and Blöschl, 2004;Driessen et al, 2010;Samuel et al, 2011;Vetter et al, 2015;Ding et al, 2016;Unduche et al, 2018;Huang et al, 2019).…”
Section: Hydrological Modelmentioning
confidence: 99%